Peran Notaris dalam Pendirian Badan Usaha Milik Desa: (BUM DESA) - Ageng Triganda Sayuti (Recital Review, 2019)
Village Owned Enterprises (BUM Desa) is an institution whose existence is mentioned in Law No. 6 of 2014 on villages to improve the village economy. The establishment of BUM Desa has many positive impacts, one of which is to increase the village's original income (PADes). From the increase of original income of the village will make the village economy and society. As a BUM Desa business entity related to third party in carrying out its economic activity. In terms of business law, a business entity is divided into legal entities and non-legal entities whose stance is made by Notaries, this paper discusses how the status of BUM Village Law agency and how the role of Notary as Public Official in the establishment of BUM Desa.